THE INFLUENCE OF MATERIALISM SELF CONTROL AND FINANCIAL ATTITUDE ON FINANCIAL MANAGEMENT BEHAVIOR IN ONLINE MARKETPLACE WITH IMPULSIVE BUYING AS AN INTERVENING VARIABLE - Kamil, Islamiah; Ariani, Meiliyah; Irawan, Indra Ade (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study uses a type of quantitative research, the aim is to determine the magnitude of the influence of Materialism Self Control and Financial Attitude Against Financial Management Behavior in Online Marketplaces with Impulsive Buying as Intervening Variables. The sample used in this study was 200 Online Marketplace Users in the Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) areas. This study uses primary data with a questionnaire. The analytical method used to test the hypothesis is path analysis The results of the study show that there is a direct effect of Materialism Self Control and Financial Attitude on Financial Management Behavior in the Online Marketplace user community. Based on the path analysis test, the results of the direct and indirect effects of Materialism Self Control and Financial Attitude on Financial Management Behavior in the Online Marketplace user community through Impulsive Buying The result shows that the direct effect is greater than the indirect effect.